Population genomics and molecular epidemiology of wheat powdery mildew in Europe - Jigisha, Jigisha; Ly, Jeanine; Minadakis, Nikolaos; Freund, Fabian; Kunz, Lukas; Piechota, Urszula; Akin, Beyhan; Balmas, Virgilio; Ben-David, Roi; Bencze, Szilvia; Bourras, Salim; Bozzoli, Matteo; et al. (PLoS biology, 2025)
Agricultural diseases are a major threat to sustainable food production. Yet, for many pathogens we know exceptionally little about their epidemiological and population dynamics, and this knowledge gap is slowing the development of efficient control strategies. Here we study the population genomics and molecular epidemiology of wheat powdery mildew, a disease caused by the biotrophic fungus Blumeria graminis forma specialis tritici (Bgt). We sampled Bgt across two consecutive years, 2022 and 2023, and compiled a genomic dataset of 415 Bgt isolates from 22 countries in Europe and surrounding regions. We identified a single epidemic unit in the north of Europe, consisting of a highly homogeneous population. Conversely, the south of Europe hosts smaller local populations which are less interconnected. In addition, we show that the population structure can be largely predicted by the prevalent wind patterns. We identified several loci that were under selection in the recent past, including fungicide targets and avirulence genes. Some of these loci are common between populations, while others are not, suggesting different local selective pressures. We reconstructed the evolutionary history of one of these loci, AvrPm17, coding for an effector recognized by the wheat receptor Pm17. We found evidence for a soft sweep on standing genetic variation. Multiple AvrPm17 haplotypes, which can partially escape recognition by Pm17, spread rapidly throughout the continent upon its introduction in the early 2000s. We also identified a new virulent variant, which emerged more recently and can evade Pm17 resistance altogether. Overall, we highlight the potential of genomic surveillance in resolving the evolutionary and epidemiological dynamics of agricultural pathogens, as well as in guiding control strategies.
Keywords: Plant Diseases; Genomics; Ascomycota; Triticum; nemoci rostlin; Europe; Genetics, Population; Evropa; pšenice; genomika; Genome, Fungal; Molecular Epidemiology; populační genetika; genom fungální; molekulární epidemiologie